2010
DOI: 10.5336/medsci.2008-8715
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Suicides Cases in Batman, South East of Turkey

Abstract: A AB BS S T TR RA AC CT T O Ob bj je ec ct ti iv ve e: : The ob jec ti ve in this pros pec ti ve study is to eva lu a te the fre qu ency, mor tality and de mog rap hic pro per ti es of su i ci des in our pro vin ce (Bat man City, Tur key). M Ma a t te e r ri i a al l a an nd d M Me et t h ho od ds s: : All ca ses of su i ci des who ad mit ted to the emer gency de part ment of the Bat man Sta te Hospi tal bet we en Ap ril 2005 and No vem ber 2007 we re inc lu ded in the study. Pa ti ents' gen der, age, his tory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In addition to these severe side effects, uncontrolled use and misuse of the antidepressive agents might cause life-threatening complications. Studies have shown that antidepressants were one of the most frequently encountered drugs in intoxication cases (11)(12)(13). Furthermore, according to the investigations, antidepressants were preferred for suicide in 74.4% attempts (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these severe side effects, uncontrolled use and misuse of the antidepressive agents might cause life-threatening complications. Studies have shown that antidepressants were one of the most frequently encountered drugs in intoxication cases (11)(12)(13). Furthermore, according to the investigations, antidepressants were preferred for suicide in 74.4% attempts (11).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that antidepressants were one of the most frequently encountered drugs in intoxication cases (11)(12)(13). Furthermore, according to the investigations, antidepressants were preferred for suicide in 74.4% attempts (11).…”
mentioning
confidence: 99%